2018
DOI: 10.1051/0004-6361/201629914
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic time-series analysis of R Canis Majoris

Abstract: R Canis Majoris is the prototype of a small group of Algol-type stars showing short orbital periods and low mass ratios. A previous detection of short-term oscillations in its light curve has not yet been confirmed. We investigate a new time series of high-resolution spectra with the aim to derive improved stellar and system parameters, to search for the possible impact of a third component in the observed spectra, to look for indications of activity in the Algol system, and to search for short-term variations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
(60 reference statements)
0
16
0
Order By: Relevance
“…As can be seen the S 1 and S 2 are in very good agreement with the corresponding synthetic spectra and their detection significance is D 1 59 and D 2 = 54, respectively. A comparison of our results and those obtained by Lehmann et al (2018) using KOREL is shown in Figure 8. As can be seen there is a very good agreement for the Primary spectrum (with an rms values of 0.01) and a satisfactory agreement for the Secondary spectrum (rms = 0.10).…”
Section: Simulation Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…As can be seen the S 1 and S 2 are in very good agreement with the corresponding synthetic spectra and their detection significance is D 1 59 and D 2 = 54, respectively. A comparison of our results and those obtained by Lehmann et al (2018) using KOREL is shown in Figure 8. As can be seen there is a very good agreement for the Primary spectrum (with an rms values of 0.01) and a satisfactory agreement for the Secondary spectrum (rms = 0.10).…”
Section: Simulation Resultsmentioning
confidence: 70%
“…In making the average of the second component estimates we used the RV star2,star1 from Lehmann et al (2018) to put all the individual S j 2 in the reference frame where RV star2 = 0. The results are shown in Figure 7: in the top panel we plot S 1 compared with the synthetic spectrum of the primary star computed using its atmospheric parameters given in (Lehmann et al 2018, Table 1), in the middle panel S 2 is compared with the corresponding synthetic spectrum, and in the bottom panel we show S 1 an S 2 ACFs. To evaluate the detection significance we show in the bottom panel also the ACF of the false S 2 we obtained by using k pairs built with two spectra both taken during the secondary eclipse.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The effect was predicted and found in photometric (e.g. Gamarova et al 2003;Mkrtichian et al 2004;Reed et al 2005) and spectroscopic (Lehmann et al 2018) observations. The dynamic eclipse mapping method was introduced by Bíró & Nuspl (2011) with the aim of NRP mode identification by reconstructing the surface intensity patterns on EBs.…”
Section: Introductionmentioning
confidence: 55%
“…The program also delivers optimised values of the RVs of the components and their radii ratio. A first successful application of the program to the short-period Algol R CMa is presented in Lehmann et al (2018); this work also includes a short description of the program algorithms and shows the advantages of LSDbinary against TOD-COR (Zucker & Mazeh 1994) in the case of very small flux ratios between the components of binary stars. We applied LSDbinary to the spectra of RZ Cas to obtain the separated LSD profiles and RVs of its components.…”
Section: Radial Velocities and Lsd Profiles With Lsdbinarymentioning
confidence: 99%
See 1 more Smart Citation